Effect of Hydrophilic Treatment of Cathode Channel on Liquid Water Transport through Gas Diffusion Layer and Performance of PEFC. (14th September 2015) - Nishida, Kosuke; Kono, Yudai; Nakamura, Takuya; Giga, Ryo
Abstract : Water flooding and plugging in cathode of polymer electrolyte fuel cells (PEFCs) lead to severe performance degradation. The aim of this study was to investigate the effect of hydrophilization of cathode channel on the liquid water transport through the gas diffusion layer (GDL) in an operating PEFC using cross-sectional visualization technique. Furthermore, the correlation between the water behavior and the cell performance was also discussed by monitoring the cell voltage and differential pressure in the cathode channel. It was noted that hydrophilic treatment of cathode channel effectively encourages liquid water suction from GDL and alleviates water flooding near catalyst layer (CL). Moreover, hydrophilization doesn't frequently cause water plugging inside gas channel.